Sustainable Water Management Strategies through Smart Technology Integration: Systematic Review - Femmilia, Femmilia; Margareth Pasule, Louisiana Elizabeth; Kusumawardhani, Amie (LifeSciFi, 2024)
This study aims to review the current literature on sustainable water management strategies in the development of Indonesia's New Capital City (Ibu Kota Nusantara/IKN) in East Kalimantan, with a particular emphasis on the integration of Smart Water Management (SWM) with the smart city concept in creating an efficient and sustainable clean water supply system. Based on the literature review conducted, it reveals that the SWM concept is an important component of the IKN vision for a modern city with the importance of implementing a smart water grid, which includes real-time water quality monitoring and leak detection to optimize water resource management. This technology not only improves efficiency but also supports the development of resilient infrastructure that is able to respond to challenges such as flooding, which is a significant problem in Indonesia. In addition, researchers advocate collaborative efforts between the government, private sector, and civil society to ensure sustainable development and effective water management strategies in the IKN. The results of the study are expected to sharpen the sustainable water management strategies that have been prepared by stakeholders in the development of the IKN and highlight the importance of integration with technology to facilitate the transition to a smart city.